Phylogenomics resolves deep subfamilial relationships in Malvaceae s.l. Issue 7 (23rd April 2021) - Cvetković, Tijana; Areces-Berazain, Fabiola; Hinsinger, Damien D; Thomas, Daniel C; Wieringa, Jan J; Ganesan, Santhana K; Strijk, Joeri S
Abstract: Malvaceae s.l., the most diverse family within Malvales, includes well-known species of great economic importance like cotton, cacao, and durian. Despite numerous phylogenetic analyses employing multiple markers, relationships between several of its nine subfamilies, particularly within the largest lineage /Malvadendrina, remain unclear. In this study, we attempted to resolve the relationships within the major clades of Malvaceae s.l. using plastid genomes of 48 accessions representing all subfamilies. Maximum likelihood and Bayesian analyses recovered a fully resolved and well-supported topology confirming the split of the family into /Byttneriina (/Grewioideae +/Byttnerioideae) and /Malvadendrina. Within /Malvadendrina, /Helicteroideae occupied the earliest branching position, followed by /Sterculioideae, /Brownlowioideae, /Tiliodeae, and /Dombeyoideae formed a clade sister to /Malvatheca (/Malvoideae +/Bombacoideae), a grouping morphologically supported by the lack of androgynophore. Results from dating analyses suggest that all subfamilies originated during hot or warm phases in the Late Cretaceous to Paleocene. This study presents a well-supported phylogenetic framework for Malvaceae s.l. that will aid downstream revisions and evolutionary studies of this economically important plant family.